Critical success factors for the successful initiation of Lean in public hospitals in KwaZulu-Natal: a factor analysis and structural equation modelling study - Logandran Naidoo; Ziska Fields (BMC, 2019)
Abstract Background Lean thinking is one of several operations-management techniques which have yet to be fully embraced in the South African health care sector. In most health care managers' service delivery mandates, what needs to be done might be known, but it is how it should be done which might be alien to most managers. In order to recognise the "how", one needs to know the critical success factors for Lean initiation. Methods The research took the form of an observational descriptive study with quantitative methods. The objectives were to identify the key variables for the successful initiation of Lean and then to conduct factor analysis and structural equation modelling (SEM) on these variables leading to the identification of critical success factors (CSFs) for Lean initiation. Simple random sampling was applied to select the participants from various categories of 500 senior managers across 73 KwaZulu-Natal (KZN) public hospitals. The sample size was 218, with a response rate of 96.8% (n = 211). For the purpose of identifying key variables for the successful initiation of Lean and then of conducting factor analysis and SEM on these variables, a self-administered, structured questionnaire was used. Data were reduced using exploratory factor analysis (EFA) to identify latent constructs. Confirmatory factor analysis (CFA) was used to determine the reliability and validity of these factors. Structural equation modelling (SEM) fit indices were then applied to assess acceptability of the measurement model. Results Certain variables were eliminated during EFA if they cross-loaded onto more than one factor, since this caused discriminant validity problems. In addition, if variables loaded weakly onto a factor, they were not retained. Three critical success factors (CSFs) were identified in this study: strategic leadership and organisational attitude; integration of Lean elements, tools, and techniques; and basic stability in operational processes. All reliability and validity conditions have been met (RMSEA = 0.085; CFI = 0.956 and χ 2/df = 2.513), consequently rendering the model reliable and valid. Conclusion None of the three CSFs can be viewed in isolation, as they all have significance at different dimensions of capability within the organisation. The use of these CSFs and the context, content, application, and outcome of Lean should be viewed in light of the organisation's strategic, technical, structural, and cultural environment. Further research in the effectiveness of these CSFs for the rollout of Lean in South African hospitals would be of benefit to the Lean body of knowledge.